ERYTHROPOIETIN AS DOPING AGENT - Nina Đukanović; Zoran Mašić; Filip Radotić; Žarko Kostovski (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2012)
Doping is the use of prohibited substances and/or methods that improve the abilities of athletes. Erythropoietin (EPO), the kidney hormone, belongs to a group of substances that are classified as blood doping, and it can be found on the list of banned substances from 1990. year. Its application leads to an increase in the number of red blood cells, which enables better supply of oxygen, and thus improve the aerobic performance of athletes. Because of that, EPO is very popular in sports where the endurance is predominantly required like a marathon, cycling, triathlon, nordic skiing. Erythropoietin can cause some adverse events, primarily to increase blood viscosity, which is associated with a higher risk of various thromboembolic complications. In detection of EPO use two groups of tests are available, through a urine sample (direct method) and blood sample (indirect method).